Association between CD14 promoter -159C/T polymorphism and the risk of sepsis and mortality: a systematic review and meta-analysis. - An-Qiang Zhang; Cai-Li Yue; Wei Gu; Juan Du; Hai-Yan Wang; Jianxin Jiang (PLoS ONE)
Background Recent studies on the association between CD14-159C/T polymorphism and sepsis showed inconclusive results. Accordingly, we conducted a comprehensive literature search and a meta-analysis to determine whether the CD14-159C/T polymorphism conferred susceptibility to sepsis or was associated with increased risk of death from sepsis. Methodology Data were collected from the following electronic databases: PubMed, Embase, Medline, Web of Knowledge, and HuGE Navigator, with the last report up to June 15, 2012. The odds ratio (OR) and 95% confidence interval (CI) were used to assess the strength of association. We summarized the data on the association between CD14-159C/T polymorphism and sepsis in the overall population and subgroup by ethnicity and sepsis subtype. Principal findings A total of 16 studies on sepsis morbidity (1369 cases and 2382 controls) and 4 studies on sepsis mortality (731 sepsis patients) met the inclusion criteria for meta-analysis. Overall analysis showed no strong evidences of association with sepsis susceptibility under any genetic model. However, slight associations were found in Asian populations (dominant model: OR = 1.38, 95%CI = 0.96-1.98, P = 0.08) and septic shock patients (dominant model: OR = 1.72, 95%CI 1.05-2.83, P = 0.03; allelic model: OR = 1.52, 95%CI 1.09-2.12, P = 0.01) in the stratified analysis. Moreover, there was borderline association between CD14-159C/T and sepsis mortality under the dominant genetic model (OR = 1.44, 95%CI = 0.98-2.11, P = 0.06). Conclusions/significance This meta-analysis suggests that the CD14-159C/T polymorphism may not be a significant susceptibility factor in the risk of sepsis and mortality. Only weak associations were observed in Asian populations and septic shock patients. More studies based on larger sample sizes and homogeneous sepsis patients are needed to confirm these findings.